Effect of desorption purge gas oxygen impurity on irreversible adsorption of organic vapors. (April 2016) - Jahandar Lashaki, Masoud; Atkinson, John D.; Hashisho, Zaher; Phillips, John H.; Anderson, James E.; Nichols, Mark; Misovski, Tony
Abstract: The effect of desorption purge gas oxygen content on activated carbon performance, specifically irreversible adsorption, was investigated. Beaded activated carbon (BAC) was tested for 5 adsorption/regeneration cycles using a mixture of nine organic compounds representing industrially-relevant organic groups. Different concentrations of oxygen (≤5–10, 000 ppm) were used in the N2 desorption purge gas. With increasing O2 concentration, mass balance cumulative heel increased by up to 35% and the fifth cycle adsorption capacity decreased by up to 55% relative to baseline scenario (≤5 ppm O2 in N2 ). Derivative thermogravimetric analysis showed heel formation due to physisorption for ≤5 ppm O2 and a combination of physisorption and chemisorption for other samples, indicating that with increasing oxygen concentration, compounds that would be physically adsorbed in highly pure N2, may instead undergo chemical reactions and become chemisorbed. Micropore surface analysis indicated increased diffusion resistance in samples regenerated in ≥625 ppm O2, likely associated with chemisorbed species. BAC samples exposed to 50 successive adsorption/regeneration cycles showed trends consistent with short-term exposure (5 cycles). The results may identify suitable purge gas purity for industrial use and explain the relationship between heel formation and purge gas purity.